Productivity and Efficiency of Banking Sector in Nepal - Hakuduwal, Kishor (Nepalese Journal of Management Science and Research, 2019)
The paper aims to analyze the productivity and efficiency of banking sector in Nepal. Using systematic random sampling, 20 banks including both commercial and development are selected. The 180 observations of nine year’s panel data from FY 2006/07 to FY 2014/15 has been used. Stochastic Frontier Approach is used taking three input variables i.e. capital, deposit and human resource cost, and one output variable i.e. loans and advance of sampled banks for analysis. The study found that the productivity of human resource, deposit and capital is significant. The joint venture banks are the most efficient than private and Government owned banks. The commercial banks are more efficient than development banks. The study has important implications for the policy makers to take corrective actions for improving the productivity and efficiency of banking sector in Nepal.